THE EFFECTS OF SOCIO-CULTURAL INTERVENTION ON PERCEIVED SOBRIETY IN SELECTED REFERRAL HOSPITALS AND REHABILITATION CENTRES IN KAMPALA AND WAKISO DISTRICTS, UGANDA. A CROSS-SECTIONAL STUDY. - Lindrio , Celestine; Kiyingi , Pio Frank; Nyende, Paul (Student’s Journal of Health Research Africa, 2024)
Background Alcohol presents a serious challenge worldwide; it is increasingly associated with negative consequences in developing countries including Uganda which bear the heaviest burden of diseases and injuries attributed to alcohol. Alcohol abuse is alarming despite the availability of treatment facilities in Uganda. The study objective was to analyze the effect of recovery interventions on perceived sobriety in Butabika National Referral Hospital and Serenity Rehabilitation Centre in the Wakiso and Kampala districts, Uganda. The post-positivist paradigm guided the study. Methods The research adopted a cross-sectional research design with a mixed-method approach known as simultaneous triangulation design. Using purposive sampling and simple random sampling, Data was collected, and questionnaires and interview guides were used. 338 subjects participated in the study. Quantitative data was analyzed using SPSS, and Pearson’s product-moment correlation coefficient was employed in hypothesis testing. Primary data was collected using self – self-administered questionnaires and Focused group discussions to obtain in-depth results. Results Sociocultural intervention and perceived sobriety have r=0.544, with a probability value p=0.000 < a=0.01 suggesting a significant correlation. The null hypothesis was rejected; which implies that sociocultural intervention significantly positively correlates with perceived sobriety at a one percent level of significance. “Culturally, alcohol is taken when twins were born and at the initiation “wall” ceremony, a day for receiving the twins into the family, the birth of a new baby, marriage introduction, paying dowry and wedding ceremonies”. Conclusion The more socio-cultural intervention is utilized in treatment facilities, the more sobriety is realized. Therefore, having workable socio-cultural intervention would help to reduce perceived sobriety. Recommendation The Ministry of Health through the mental health desk office encourages mental health practitioners to empower therapists in the treatment facilities to give more attention to using sociocultural intervention to address beliefs about excessive use of alcohol.